Patients Undergoing Ileoanal Pouch Surgery Experience a Constellation of Symptoms and Consequences Representing a Unique Syndrome A Report From the Patient-Reported Outcomes After Pouch Surgery (PROPS) Delphi Consensus Study - Cavallaro Paul; Fearnhead Nicola; Bissett Ian; Brar Mantaj; Cataldo Thomas; Clarke Rasheed; Denoya Paula; Elder Amber L.; Gecse Krisztina B.; Hendren Samantha; Holubar Stefan; Jeganathan Nimalan; et al. (2021)
The primary aim was to create a patient-centered definition of core symptoms that should be included in future studies of pouch function.Functional outcomes after ileoanal pouch creation have been studied; however, there is great variability in how relevant outcomes are defined and reported. More importantly, the perspective of patients has not been represented in deciding which outcomes should be the focus of research.Expert stakeholders were chosen to correlate with the clinical scenario of the multidisciplinary team that cares for pouch patients: patients, colorectal surgeons, gastroenterologists/other clinicians. Three rounds of surveys were employed to select high-priority items. Survey voting was followed by a series of online patient consultation meetings used to clarify voting trends. A final online consensus meeting with representation from all 3 expert panels was held to finalize a consensus statement.One hundred ninety-five patients, 62 colorectal surgeons, and 48 gastroenterologists/nurse specialists completed all 3 Delphi rounds. Fifty-three patients participated in online focus groups. One hundred sixty-one stakeholders participated in the final consensus meeting. On conclusion of the consensus meeting, 7 bowel symptoms and 7 consequences of undergoing ileoanal pouch surgery were included in the final consensus statement.This study is the first to identify key functional outcomes after pouch surgery with direct input from a large panel of ileoanal pouch patients. The inclusion of patients in all stages of the consensus process allowed for a true patient-centered approach in defining the core domains that should be focused on in future studies of pouch function.
Keywords: Klinikai orvostan